An Analysis of How Language Usage Show Systematic Pattern of Variation Based on Linguistics and Social Factors - Reni Safira; Putri Bayat; Azalia, Ataillah Calista; Alya, Cania Henfaridja (VISA: Journal of Vision and Ideas, 2024)
This study aims to determine the pattern of systematic variation in language use based on social and linguistic factors seen from a pragmatic point of view. This type of research uses qualitative research methods. The data collection technique used in this study is a library research method that focuses on the study of various literature by analyzing the content in it. In addition, the data collection research used in this study was observation and interviews. The data analysis technique used is a content analysis technique. The research sample in this article is the people from Medan. Based on the results of the research that language can affect systematic variation based on social and linguistic factors. Based on pragmatic linguistic factors, language use can influence systematic variation due to several factors, such as habitual factors, environmental factors, and interest factors in certain language styles. While social factors can affect systematic variations in language use, especially occupational factors, because the work environment greatly determines how a person's language style in everyday life.This study aims to determine the pattern of systematic variation in language use based on social and linguistic factors seen from a pragmatic point of view. This type of research uses qualitative research methods. The data collection technique used in this study is a library research method that focuses on the study of various literature by analyzing the content in it. In addition, the data collection research used in this study was observation and interviews. The data analysis technique used is a content analysis technique. The research sample in this article is the people from Medan. Based on the results of the research that language can affect systematic variation based on social and linguistic factors. Based on pragmatic linguistic factors, language use can influence systematic variation due to several factors, such as habitual factors, environmental factors, and interest factors in certain language styles. While social factors can affect systematic variations in language use, especially occupational factors, because the work environment greatly determines how a person's language style in everyday life.